Spegazzinia camelliae sp. nov. (Didymosphaeriaceae, Pleosprales), a new endophytic fungus from northern Thailand - Suwannarach, Nakarin; Kumla, Jaturong; Lumyong, Saisamorn (Phytotaxa, 2021)
A new endophytic ascomycete, described herein as Spegazzinia camelliae, was isolated from leaves of Camellia sinensis var. assamica collected from Nan Province, Thailand. This species is characterized by basauxic conidiophores and dark brown to blackish brown α and β conidia. It can be distinguished from previously described Spegazzinia species by the spine length of the α conidia and the size of the β conidia. Multi-gene phylogenetic analyses of the small subunit (SSU), large subunit (LSU) and internal transcribed spacers (ITS) of the nuclear ribosomal DNA (rDNA) and the translation elongation factor 1-alpha (tef1) genes also support S. camelliae is a distinct new species within Spegazzinia. A full description, color photographs, illustrations and a phylogenetic tree showing the position of S. camelliae are provided.